N+32=67

Simple and best practice solution for N+32=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for N+32=67 equation:


Simplifying
N + 32 = 67

Reorder the terms:
32 + N = 67

Solving
32 + N = 67

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-32' to each side of the equation.
32 + -32 + N = 67 + -32

Combine like terms: 32 + -32 = 0
0 + N = 67 + -32
N = 67 + -32

Combine like terms: 67 + -32 = 35
N = 35

Simplifying
N = 35

See similar equations:

| 5k-12=k | | -1+8k=79 | | 0.6667(x+13)=22 | | 5(-7x+2)=270 | | 4+21x=2.50 | | -110+8x=30+x | | 625x^4=1000x^3 | | Z-5=-11 | | -32=6x+4x+8 | | -14=2(w-3)-4w | | 6x+10=6x+94 | | (X+3)(x+6)=189 | | x+ywhenx=3 | | 1. 6x+10=6x+94 | | (b^7)^2/7 | | 3m+6=6m-3 | | -67=-(j-(-22)) | | 4(2+7x)=204 | | D=1/2mq | | 1. 4(2+7x)=204 | | -5(x-10)=-36 | | K-3/4=4 | | 1/6k=-2/3 | | 4v+12=56 | | X=-9+3y | | -4(-9+6x)=84 | | 6y+6=8y-16 | | y+8=2(4x+4) | | 5n+34=-4(1-7n) | | 24+4=16 | | -6x+12y=-6 | | 7-18=-116 |

Equations solver categories